2020
DOI: 10.2471/blt.19.249565
|View full text |Cite
|
Sign up to set email alerts
|

Field-testing of primary health-care indicators, India

Abstract: Objective To develop a primary health-care monitoring framework and health outcome indicator list, and field-test and triangulate indicators designed to assess health reforms in Kerala, India, 2018–2019. Methods We used a modified Delphi technique to develop a 23-item indicator list to monitor primary health care. We used a multistage cluster random sampling technique to select one district from each of four district clusters, and then select both a family and a primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Filling this gap, we sought to examine inequalities in testing and self-reported prevalence of HBP and HBG by education, wealth, caste and tribes and religion separately for men and women in Kerala. We drew upon a health systems survey undertaken to monitor the performance of Kerala’s Aardram health reform initiatives as a part of a larger implementation research study assessing equity in Universal Health Coverage reforms in the state [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Filling this gap, we sought to examine inequalities in testing and self-reported prevalence of HBP and HBG by education, wealth, caste and tribes and religion separately for men and women in Kerala. We drew upon a health systems survey undertaken to monitor the performance of Kerala’s Aardram health reform initiatives as a part of a larger implementation research study assessing equity in Universal Health Coverage reforms in the state [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…The government of Kerala has significantly revamped the primary care in the public health system by introducing family health centres (FHCs) with electronic health records (eHealth) [8,9]. For people with diabetes, a comprehensive diabetes care plan was initiated about five years ago, and it includes screening for all complications of diabetes except DR [10]. Therefore, implementing a DR screening programme within the primary care not only provides a complete preventive medicine plan for people with diabetes but also contributes to achieving some of the Sustainable Development Goals (SDG) [11].…”
Section: Introductionmentioning
confidence: 99%
“…More than reflecting testing, this perhaps pertains to the relationship between these other variables and socioeconomic status in general (i.e., the recursively and strength of relationship between wealth (inequality) and caste as well as wealth (inequality) and education may be greater than that between wealth (inequality) and sex or religion per se). Research in northern India has found that males were being excluded from population-based screening efforts, hypothesized to be attributed to the emphasis of health systems on maternal and child care in those regions [38]. Given that NCD control programs have been longer running in India's southern states like Kerala, the lack of sex and religion-based exclusion warrants further study and may offer insights for programming in other parts of the country.…”
Section: Discussionmentioning
confidence: 99%
“…Th inclusion criteria was decided as household which had at least one member above 30 years. The detailed sampling design, survey method, data collection, sample size calculation and data processing are reported elsewhere [32,38].…”
Section: Study Design and Settingmentioning
confidence: 99%